(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper aims to study the necessity of financial inclusion in India with reference to Pradhan MantrijanDhanYojana.The sustainable growth of a developing coutry like India is only possible through the financial inclusion as providing financial services to all the people.PradhanMantri Jan DhanYojana is an ambitious scheme for the biggest financial inclusion in the world.This scheme was announced by the Hon’ble Prime Minister Narendra Modi on 15th August 2014 and it was launced on 28th August 2014